Cu (II) (picolinyl-L-tryptophan) 2 is an effecient multifunctional radioprotector - T. Zh. Hovsepyan (ՀՀ ԳԱԱ հրատ.)
Ionizing radiation (IR) exposure is triggering inflammation and increased rate of apoptosis leading to generation of tissue damaging agents and cell death. In the present study we investigated the effects of potential radioprotector, copper complex of L-tryptophan Schiff base derivative, Cu(II)(picolinyl-L-tryptophan)2, on the blood levels of inflammatory and apoptotic markers, prostaglandin-E2 and B-cell lymphoma 2-associated X protein, circulating immune complexes and key enzymes of the native antioxidant system superoxide dismutase and catalase in animal model of ionizing radiation. Իոնիզանցնող ճառագայթումը (ԻՃ) առաջացնում է բորբոքային պրոցեսներ և բարձրացնում ապոպտոզի մակարդակը, ինչը հանգեցնում է հյուսվածք վնասող գործոնների ձևավորմանը և բջջի մահվան: Աշխատանքում մենք ուսումնասիրել ենք պոտենցիալ ռադիոպաշտպանիչ միացության` L-տրիպտոֆանի Շիֆֆի հիմքի ածանցյալ Cu(II)(պիկոլինիլ-L-տրիպտոֆանատ)2-ի ազդեցությունը կենդանի մոդելների արյան մեջ բորբոքային և ապոպտոտիկ մարկերների` պրոստագլանդին E2-ի, B բջջային լիմֆոմայի հետ ասոցիացված X սպիտակուցի, շրջանառու իմունային համալիրների և բնական հակաօքսիդանտային համակարգի առանցքային ֆերմենտների` սուպերօքսիդդիսմուտազի և կատալազի մակարդակների վրա իոնիզացնող ճառագայթման պայմաններում: Ионизирующая радиация (ИР) вызывает воспаление и повышает уровень апоптоза, что приводит к образованию разрушающих ткань факторов и гибели клетки. Нами исследовано влияние потенциального радиопротектора производного Шиффового основания L- триптофана, Cu(II)(пиколинил-L-триптофаната)2 на уровни маркеров воспаления и апоптоза, простагландина-Е2, X белка ассоциирующего с лимфомой B- клеток, циркулирующих иммунных комплексов, и ключевых ферментов антиоксидантной системы супероксиддисмутазы и каталазы в крови у животных, подвергшихся влиянию ИР.
Keywords: Biology; Molecular Biology